Effects of a backward running training on backward peak velocity running, V̇O2max, vVO2max and 3 km forward running performance in male adults: a pilot study - Alessandra Precinda Kauffman; Gabriel Henrique Ornaghi de Araujo; Francisco de Assis Manoel; Cecília Segabinazi Peserico; Fabiana Andrade Machado (Motriz: Revista de Educacao Fisica, 2021)
Abstract Aims: The study aimed to evaluate the effects of a backward running (BR) training program prescribed by the peak backward running velocity (Vpeak_BR) on physiological variables and a 3 km forward running (FR) performance. Methods: Eight untrained running male adults in running took place in the study. All the participants underwent five weeks of BR training prescribed based on Vpeak_BR. They performed a maximal incremental test on the treadmill to determine the maximal oxygen uptake (V̇O2max) and the velocity associated with V̇O2max (vV̇O2max). The participants were also tested on the track field to determine the Vpeak_BR and undertook a 3 km FR performance. All initial assessments were also performed after the training period. Results: The results showed statistically significant improvements in 3 km FR performance (14.2 ± 1.2 min vs. 13.5 ± 1.0 min) and Vpeak_BR (8.0 ± 0.8 km·h−1 vs. 8.5 ± 0.5 km·h−1) after the training period. Conclusion: BR training effectively improved 3 km FR performance and Vpeak_BR, demonstrating that Vpeak_BR determined according to the protocol proposed in this study can be used for the prescription of BR training. Further, BR training represents an effective training method that can be inserted into an FR running training program.